Usefulness of the 2-Devices-in-1-Channel Method in Case of Difficult Selective Biliary Cannulation Due to Parapapillary Diverticulum/Diverticular Papilla. Issue 5 (October 2018) - Sakai, Yuji; Tsuyuguchi, Toshio; Sugiyama, Harutoshi; Mikata, Rintaro; Ohyama, Hiroshi; Yasui, Shin; Nakamura, Masato; Takahashi, Koji; Kumagai, Junichjiro; Yamato, Mutsumi; Kusakabe, Yuko; Shingyoji, Ayako; et al.
Abstract : Purpose: To investigate whether the 2-devices-in-1-channel method is useful for selective biliary cannulation in patients with parapapillary diverticulum or intradiverticular papilla, where the papilla cannot be seen from the front. Materials and Methods: Biliary cannulation using the 2-devices-in-1-channel method was performed in 28 patients who presented difficulty due to parapapillary diverticulum or intradiverticular papilla. There were 15 men and 13 women whose mean age was 68.8 (58 to 88) years. There were 22 patients with common bile duct stones, 5 with pancreatic cancer, and 1 with gallbladder cancer. Results: Selective biliary cannulation was successful in all 28 patients. Common bile duct stones could be removed in all 22 patients after endoscopic sphincterotomy or endoscopic balloon dilation, and all 5 patients with pancreatic cancer as well as the patient with gallbladder cancer were successfully drained. There were no procedure-related complications. Conclusions: From these results, we consider the 2-devices-in-1-channel method is useful and safe to perform selective biliary cannulation when the papilla cannot be seen from the front due to parapapillary diverticulum, or intradiverticular papilla.